Potencial fungicida de extrato foliar de Cariocar Villosum (AUBL.) Pers (Caryocaraceae) - Valente, Paula Mara Rodrigues (2012)
The use of fungicides is in many cases the only viable and effective measure to control diseases and ensure the sustainability of agriculture. On the other hand, it is also a technology that brings negative impacts to the environment and public health. The fungus Fusarium sp. cause severe damage to crops of vegetables in the city of Parintins - Am is considered soil pathogen capable of causing severe damage to many economically important agricultural species. In this context, the species Caryocar villosum (piquiá) appears as a promising possibility because preliminary studies reveal the existence of substances with fungicidal and / or fungistatic. This study aimed to obtain crude extracts ethanol, methanol and aqueous leaves C. villosum, and analyze their activity on the fungus Fusarium sp. Using two modes of extraction, hot and cold. From leaves of lettuce necrotic been made to isolate Fusarium sp. Which was cultivated in BDA. Foram The effects of the extracts on o crescimento mycelial concentrations 1g / L, 5g / L, 10g / L and 15g / L measuring the diameter of fungal colonies for seven days. For counting was used ten cellophane disks of 0.8 cm in diameter which were placed in petri dishes on three discs of filter paper soaked in solution at concentrations of extracts 1g / L, 5g / L, 10g / L and 15g / L in triplicate. At concentrations of 10 and 15g / L of ethanol extract hot, significant inhibitions were observed in mycelial growth of the fungus. Concentrations 5, 10 and 15 g / L of hot aqueous ethanol extract and significant inhibitions were observed on conidial germination of Fusarium held from 16h incubation. Key words: Caryocar villosum, a fungicide, Fusarium sp.